Polyurethane material, biodegradable polyurethane medical examination gloves and preparation method of biodegradable polyurethane medical examination gloves

By adding polylactic acid-TiO2 and modified ferulic acid to the polyurethane material, a stable aqueous polyurethane emulsion is formed, which solves the problem of insufficient degradation performance of nitrile rubber gloves, and improves high mechanical properties and biodegradability. Meet environmental protection requirements.

CN119192824AInactive Publication Date: 2024-12-27SHANDONG JINGHUAJIAN MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411399894.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The degradation and mechanical properties of existing nitrile rubber gloves are insufficient and do not meet environmental protection requirements. The addition of degradable additives to the prior art still needs to further improve the degradation rate and elongation of breakage.

Method used

Using aqueous polyurethane materials, by adding polylactic acid-TiO2, modified ferulic acid and hydrophobic particles to the polyurethane emulsion, a stable aqueous polyurethane emulsion is formed, which improves the mechanical properties and biodegradability of the material, and passes the complexity of polylactic acid-TiO2. Cytoplasmic blocks improve biodegradability.

Benefits of technology

The mechanical properties and biodegradability of polyurethane materials have been significantly improved, the degradation rate and antibacterial effect have been improved, the leakage performance has been reduced, and the stability and biodegradability of the materials have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192824A_ABST
    Figure CN119192824A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane materials, in particular to a polyurethane material, biodegradable polyurethane medical examination gloves and a preparation method of the biodegradable polyurethane medical examination gloves. Comprising the following raw materials in parts by weight: 80 to 100 parts of waterborne polyurethane emulsion, 8 to 12 parts of polylactic acid-TiO2, 0.6 to 1 part of 4-maleimido phenol, 0.06 to 0.1 part of a dispersing agent NNO, 1 to 2 parts of zinc oxide, 1 to 2 parts of ethylenediamine and 20 to 30 parts of deionized water. The urethane material can effectively improve the degradation performance, the mechanical performance and the antibacterial performance of the biodegradable polyurethane medical examination gloves prepared from the polyurethane material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane materials, and in particular to a polyurethane material, a biodegradable polyurethane medical examination glove and a preparation method thereof. Background Art

[0002] Waterborne polyurethane is a new type of polyurethane system that uses water instead of organic solvent as a dispersion medium, also known as water-dispersed polyurethane, water-based polyurethane or water-based polyurethane. Waterborne polyurethane uses water as a solvent, has the advantages of being pollution-free, safe and reliable, having excellent mechanical properties, good compatibility, and being easy to modify, and is widely used in coatings, adhesives, fabric coatings and finishing agents, leather finishing agents, paper surface treatment agents, and fiber surface treatment agents. Compared with nitrile gloves, waterborne polyurethane gloves have better softness, hygroscopicity and breathability, while also taking into account corrosion resistance, solvent resistance and biocompatibility, and are ideal materials for replacing nitrile rubber. Moreover, rubber gloves waste products based on nitrile rubber cannot be degraded by means of biological burial, and are mainly processed by landfill or incineration, which does not meet the requirements of environmental protection. In order to solve the degradation problem of nitrile rubber, most of the prior art uses the method of adding degradable additives to improve the degradation performance of nitrile rubber. For example, the prior art discloses a biodegradable nitrile medical glove and a preparation method thereof, which improves the degradation performance of the nitrile medical gloves by adding a biodegradable acrylonitrile grafted starch component that is compatible with nitrile latex to the emulsion formula, but the degradation rate and elongation at break still need to be further improved. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a polyurethane material, a biodegradable polyurethane medical examination glove and a preparation method thereof.

[0004] The present invention is achieved through the following technical solutions: A polyurethane material comprises the following raw materials in parts by weight: 80-100 parts of aqueous polyurethane emulsion, polylactic acid-TiO 2 8-12 parts, 4-maleimidophenol 0.6-1 parts, dispersant NNO 0.06-0.1 parts, zinc oxide 1-2 parts, ethylenediamine 1-2 parts, deionized water 20-30 parts.

[0005] Furthermore, the preparation method of the aqueous polyurethane emulsion comprises the following steps: (1) dehydrating castor oil under vacuum at 100° C. for 2 h, adding isophorone diisocyanate, polytetramethylene glycol and dibutyltin dilaurate, stirring at 60° C. and 200-300 rpm for 2-3 h under nitrogen protection, adding dimethylolpropionic acid, reacting at 70° C. for 2 h, adding acetone to an acetone concentration of 10-15 wt%, reducing the concentration to room temperature, and adding triethylamine to obtain a prepolymer; (2) Mixing silica with tetrahydrofuran, ultrasonicating at 300 W for 20-30 min, adding 3-aminopropyltriethoxysilane (APTES), heating in a water bath at 70°C for 5-6 h, standing at 4°C for 2 h, centrifuging at 8000 rpm for 15-20 min, and drying the precipitate at 60°C to obtain modified silica; (3) Methyl ferulate was dissolved in DMF, KOH was added under stirring, and the mixture was reacted for 1 h. Methyl iodide was added and the mixture was heated to 60 °C for 2 h. Deionized water was added and the mixture was extracted with ethyl acetate three times. The organic phases were combined and washed with saturated NaCl solution. 2 SO 4 The obtained product was dissolved in anhydrous ethanol, and a 2 mol / L NaOH aqueous solution was added, and stirred at 70°C for 6 h, 10 -3 Mpa, 60℃, concentrated under reduced pressure for 3-4 h, adjusted the pH to 1.8-2.2 with 2mol / L hydrochloric acid solution, filtered, washed the filter cake with ethanol and deionized water, and dried at 80℃ to obtain modified ferulic acid; (4) tetrahydrofuran and the modified ferulic acid obtained in step (3) are mixed to obtain a modified ferulic acid solution, N,N'-carbonyldiimidazole (CDI) is dissolved in tetrahydrofuran to obtain a CDI solution, the CDI solution is added dropwise to the modified ferulic acid solution under nitrogen protection, the dropping speed is 0.8-1.2 mL / min, after the dropwise addition is completed, the mixture is stirred at 60-80 rpm for 4-5 h at room temperature, the modified silica obtained in step (2) is added, the mixture is stirred for 5-6 h, the mixture is centrifuged at 8000-10000 rpm for 20 min, the precipitate is washed with distilled water for 4-6 times, and dried at 80°C to obtain hydrophobic particles; (5) The hydrophobic particles described in step (4) are mixed with deionized water, and ultrasonicated at 500-600 W for 40-60 min to obtain a hydrophobic particle dispersion, and the hydrophobic particle dispersion is mixed with the prepolymer obtained in step (1), and emulsified at 8000-10000 rpm for 2 h to obtain an aqueous polyurethane emulsion.

[0006] Furthermore, in step (1), the molecular weight of the polytetrahydrofuran ether glycol is 1500.

[0007] Furthermore, in step (1), the dibutyltin dilaurate accounts for 0.8-1.2wt% of the total mass of castor oil, polytetramethylene ether glycol and isophorone diisocyanate.

[0008] Furthermore, in step (1), the molar ratio of the isocyanate group of isophorone diisocyanate: the hydroxyl group in dehydrated castor oil: the hydroxyl group of polytetramethylene ether diol: the hydroxyl group of dimethylol propionic acid: the hydroxyl group in triethylamine is 2.5-3:1-1.5:1:0.6-1:0.8-1.2.

[0009] Furthermore, in step (2), the silica particle size is 200-300 nm.

[0010] Furthermore, in step (2), the ratio of silicon dioxide to tetrahydrofuran is 1 g:40 mL.

[0011] Furthermore, in step (2), the mass ratio of APTES to silicon dioxide is 3:1.

[0012] Furthermore, in step (3), the ratio of methyl ferulate to DMF is 1 g:8-10 mL.

[0013] Furthermore, in step (3), the mass ratio of methyl ferulate to KOH is 2.5:1.

[0014] Furthermore, in step (3), the mass ratio of methyl iodide to methyl ferulate is 4:5-6.

[0015] Furthermore, in step (3), the volume ratio of deionized water to DMF is 5:1.

[0016] Furthermore, in step (3), the ratio of the dried product to anhydrous ethanol is 1 g:35-40 mL.

[0017] Furthermore, in step (3), the volume ratio of the NaOH aqueous solution to anhydrous ethanol is 5:1.

[0018] Furthermore, in step (4), the ratio of modified ferulic acid to tetrahydrofuran in the modified ferulic acid solution is 1 g:5 mL.

[0019] Furthermore, in step (4), the ratio of CDI to tetrahydrofuran in the CDI solution is 1:10-15 mL.

[0020] Furthermore, in step (4), the mass ratio of the modified ferulic acid to CDI is 1:0.4-0.6.

[0021] Furthermore, in step (4), the mass ratio of the modified silicon dioxide to the modified ferulic acid is 1:2-3.

[0022] Furthermore, in step (5), the ratio of the hydrophobic particles to deionized water is 1 g:50 mL.

[0023] Furthermore, in step (5), the mass ratio of the hydrophobic particle dispersion to the prepolymer is 1:2-3.

[0024] Furthermore, the polylactic acid-TiO 2 The preparation method comprises the following steps: (a) 3-aminopropyltrimethoxysilane (APTMS) and succinic anhydride were added to DMF and mixed, and stirred at 200-300 rpm for 3 h at 0-4 ° C, and titanium dioxide DMF suspension after 500W ultrasonic dispersion for 20 min was added, and deionized water was added at the same time. After stirring for 5 h, the mixture was centrifuged at 10000 rpm for 30 min, and the precipitate was washed with anhydrous ethanol for 5-7 times, and dried at 80 ° C to obtain carboxylated titanium dioxide; (b) The carboxylated titanium dioxide and gallic acid obtained in step (a) were added to DMF, p-toluenesulfonic acid was added, and the mixture was heated at 50°C for 3-4 h, and then at 60°C for 10 -3 MPa for 2-3 h, add deionized water, centrifuge at 10000 rpm for 30 min, and dry the precipitate at 80-100 °C to obtain modified titanium dioxide; (c) Under nitrogen protection, part of the L-lactic acid is dehydrated at 110-130°C and a vacuum degree of -0.08 to -0.1 MPa for 2-3 h, p-toluenesulfonic acid is added, and the reaction is carried out at 150-170°C and a vacuum degree of -0.08 to -0.12 MPa for 2-3 h; (d) After the reaction in step (c) is completed, the remaining L-lactic acid, the modified titanium dioxide obtained in step (a) and deionized water are added, and the reaction is carried out at 160-180°C for 1-2 h, and at 210-230°C for 2 h. The mixture is cooled to room temperature, centrifuged at 10000 rpm for 15-20 min, and the precipitate is washed with acetone 3 times, washed with anhydrous ethanol 3 times, and dried in vacuum at 60°C to obtain polylactic acid-TiO 2 .

[0025] Furthermore, in step (a), the mass ratio of APTMS to succinic anhydride is 9:5.

[0026] Furthermore, in step (a), the usage ratio of APTMS to DMF is 1 g:20 mL.

[0027] Furthermore, in step (a), the titanium dioxide particle size is 40-60 nm.

[0028] Furthermore, in step (a), in the titanium dioxide DMF suspension, the dosage ratio of titanium dioxide to DMF is 1:30 mL.

[0029] Furthermore, in step (a), the ratio of the titanium dioxide DMF suspension to APTMS is 15 mL:1 g.

[0030] Furthermore, in step (a), the volume ratio of the deionized water to the titanium dioxide DMF suspension is 2-3:25.

[0031] Furthermore, in step (b), the ratio of carboxylated titanium dioxide, gallic acid and DMF is 3-5 g: 1 g: 30-40 mL.

[0032] Furthermore, in step (b), the mass ratio of p-toluenesulfonic acid to gallic acid is 1:12-15.

[0033] Furthermore, in step (b), the volume ratio of deionized water to DMF is 2:1.

[0034] Furthermore, in step (c), the amount of L-lactic acid used is 60-70wt% of the total amount.

[0035] Furthermore, in step (c), the mass ratio of p-toluenesulfonic acid to L-lactic acid is 1-2 mg:1 g.

[0036] Furthermore, the mass ratio of the total amount of L-lactic acid to the modified titanium dioxide is 12-15:1.

[0037] Furthermore, in step (d), the ratio of deionized water to modified titanium dioxide is 1 g:20 mL.

[0038] Furthermore, the present invention also provides a biodegradable polyurethane medical examination glove, which is prepared from the polyurethane material.

[0039] Furthermore, the present invention also provides a method for preparing the biodegradable polyurethane medical examination gloves, comprising the following steps: S1: Mix water-based polyurethane emulsion, polylactic acid-TiO 2 , 4-maleimidophenol, dispersant NNO, zinc oxide, ethylenediamine and deionized water are mixed, and stirred at 300-400 rpm for 20-30 min to obtain a polyurethane material; S2: After drying the glove mold impregnated with the coagulant at 100-120°C, when the temperature reaches 30-50°C, impregnate it into the polyurethane material obtained in step S1, leave it for 40-60s, dry it at 80-110°C for 20-30 min, and go through the processes of crimping and demoulding to obtain biodegradable polyurethane medical examination gloves.

[0040] Furthermore, the coagulant is a calcium chloride aqueous solution with a concentration of 8-12wt%.

[0041] Compared with the prior art, the present invention has the following beneficial effects: The waterborne polyurethane emulsion of the present invention uses diisocyanate and castor oil polytetrahydrofuran ether diol as polymerization monomers, forms polyurethane through chain extension reaction under the action of dimethylol propionic acid, a chain extender containing a hydrophilic group (hydroxyl group), and is neutralized into salt under the action of triethylamine, a neutralizing agent, to further enhance the hydrophilicity of the polyurethane hydrophilic group, which is beneficial to the hydrophilic and hydrophobic self-assembly in the emulsification process, and forms polyurethane microparticles with a hydrophobic core and a hydrophilic shell, and the hydrophobic particles are encapsulated in the hydrophobic core of the polyurethane microparticles to form a stable waterborne polyurethane emulsion. Among them, castor oil contains a polyhydroxy structure, which can improve the crosslinking degree of the waterborne polyurethane to a certain extent, and improve the water resistance and mechanical properties of the waterborne polyurethane. The present invention combines hydrophobic alkyl groups with ferulic acid to obtain modified ferulic acid, which can effectively improve hydrophobicity. Amino groups are introduced into the surface of silica, and modified ferulic acid is grafted onto the surface with the amino groups as binding sites to obtain hydrophobic particles, which significantly improves hydrophobicity and dispersibility and prevents agglomeration. The hydrophobic particles of the present invention have small particle size, good dispersibility and good emulsification effect. The hydrophobic particles are encapsulated in the hydrophobic core of polyurethane particles to form a stable aqueous polyurethane emulsion, which can improve the mechanical properties of polyurethane materials. The present invention prepares polylactic acid-TiO 2 , can be cross-linked with waterborne polyurethane to increase the degree of cross-linking, thereby improving the water resistance and mechanical properties of polyurethane materials; polylactic acid-TiO 2 The polylactic acid, gallic acid and titanium dioxide which have antibacterial properties can be used to synergistically enhance the antibacterial effect. The invention carboxylates titanium dioxide and uses gallic acid to modify it to obtain modified titanium dioxide. Gallic acid contains multiple hydroxyl groups and carboxyl groups, so that the modified titanium dioxide can participate in the polymerization reaction of lactic acid and become a block in the modified polylactic acid molecular chain. The modified titanium dioxide has better stability and is not easy to precipitate in the later stage. The invention first polycondenses to obtain polylactic acid with a certain degree of polymerization to ensure the initial formation of the polymer chain. The modified titanium dioxide is added during the subsequent polymerization because the premature participation of the modified titanium dioxide in the polycondensation will affect the structure of the polymer molecular chain, thereby affecting the performance of the polylactic acid. The modified titanium dioxide is added after the pre-polycondensation because the polymer chain has been formed, so the influence is small. The polylactic acid-TiO 2 The hybrid blocks contain modified titanium dioxide, which serve as sites, making the material more biodegradable. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 The antibacterial properties of the polyurethane materials described in Examples 1-3 and Comparative Examples 1-2 of the present invention; Figure 2 The antibacterial properties of the polyurethane materials described in Examples 1-3 and Comparative Examples 1-2 of the present invention after accelerated testing; Figure 3 The degradability of the polyurethane materials described in Examples 1-3 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention are purchased through commercial channels.

[0045] Example 1: This example provides a polyurethane material, comprising the following raw materials in parts by weight: 100 parts of aqueous polyurethane emulsion, polylactic acid-TiO 2 12 parts, 4-maleimidophenol 1 part, dispersant NNO 0.1 parts, zinc oxide 2 parts, ethylenediamine 2 parts, deionized water 30 parts.

[0046] The preparation method of waterborne polyurethane emulsion comprises the following steps: (1) Castor oil is dehydrated under vacuum at 100° C. for 2 h, isophorone diisocyanate, polytetramethylene glycol with a molecular weight of 1500 and dibutyltin dilaurate are added, the dibutyltin dilaurate accounts for 1.2 wt% of the total mass of castor oil, polytetramethylene glycol and isophorone diisocyanate, the mixture is stirred at 60° C. and 300 rpm for 3 h under nitrogen protection, dimethylolpropionic acid is added, the mixture is reacted at 70° C. for 2 h, acetone is added until the acetone concentration is 15 wt%, the mixture is cooled to room temperature, triethylamine is added, and the molar ratio of isocyanate group of isophorone diisocyanate: hydroxyl group in dehydrated castor oil: hydroxyl group in polytetramethylene glycol: hydroxyl group in dimethylolpropionic acid: hydroxyl group in triethylamine is 3:1.5:1:1:1.2, to obtain a prepolymer; (2) 1 g of 300 nm silica was mixed with 40 mL of tetrahydrofuran, ultrasonicated at 300 W for 30 min, 3 g of 3-aminopropyltriethoxysilane (APTES) was added, heated in a 70 °C water bath for 6 h, allowed to stand at 4 °C for 2 h, centrifuged at 8000 rpm for 20 min, and the precipitate was dried at 60 °C to obtain modified silica; (3) Dissolve 7.5 g of methyl ferulate in 75 mL of DMF, add 3 g of KOH with stirring, react for 1 h, add 5 g of methyl iodide, heat to 60 °C and react for 2 h, add 375 mL of deionized water, extract three times with ethyl acetate, combine the organic phases, wash the organic phases with saturated NaCl solution, and then add anhydrous Na 2 SO 4 The solvent was evaporated at 90 °C and dried at 100 °C. 1 g of the obtained dried product was dissolved in 40 mL of anhydrous ethanol, 200 mL of 2 mol / L NaOH aqueous solution was added, and the mixture was stirred at 70 °C for 6 h and 10 -3 Mpa, 60℃, concentrated under reduced pressure for 4 h, adjusted the pH to 2.2 with 2 mol / L hydrochloric acid solution, filtered, washed the filter cake with ethanol and deionized water, and dried at 80℃ to obtain modified ferulic acid; (4) 15 mL of tetrahydrofuran and 3 g of the modified ferulic acid obtained in step (3) were mixed to obtain a modified ferulic acid solution, 1.8 g of N,N'-carbonyldiimidazole (CDI) was dissolved in 27 mL of tetrahydrofuran to obtain a CDI solution, and the CDI solution was added dropwise to the modified ferulic acid solution under nitrogen protection at a dropping rate of 1.2 mL / min. After the addition was completed, the mixture was stirred at 80 rpm for 5 h at room temperature, and then 1 g of the modified silica obtained in step (2) was added, and the mixture was stirred for 6 h. The mixture was centrifuged at 10,000 rpm for 20 min, and the precipitate was washed 6 times with distilled water and dried at 80°C to obtain hydrophobic particles. (5) 1 g of the hydrophobic particles described in step (4) was mixed with 50 mL of deionized water, and ultrasonicated at 600 W for 60 min to obtain a hydrophobic particle dispersion. 10 g of the hydrophobic particle dispersion was mixed with 30 g of the prepolymer obtained in step (1), and emulsified at 10,000 rpm for 2 h to obtain an aqueous polyurethane emulsion.

[0047] Polylactic acid-TiO 2 The preparation method comprises the following steps: (a) 9 g 3-aminopropyltrimethoxysilane (APTMS) and 5 g succinic anhydride were added to 180 mL DMF and mixed. The mixture was stirred at 300 rpm for 3 h at 4 °C. 135 mL 60 nm titanium dioxide was added and mixed with DMF at a ratio of 1 g:30 mL. The titanium dioxide DMF suspension was obtained by ultrasonic dispersion at 500 W for 20 min. 16.2 mL deionized water was added at the same time. The mixture was stirred for 5 h and centrifuged at 10,000 rpm for 30 min. The precipitate was washed with anhydrous ethanol for 7 times and dried at 80 °C to obtain carboxylated titanium dioxide. (b) 15 g of the carboxylated titanium dioxide obtained in step (a) and 3 g of gallic acid were added to 120 mL of DMF, 0.2 g of p-toluenesulfonic acid was added, and the mixture was heated at 50°C for 4 h, and then at 60°C for 10 h. -3 MPa for 3 h, add 240 mL of deionized water, centrifuge at 10000 rpm for 30 min, and dry the precipitate at 100 °C to obtain modified titanium dioxide; (c) Under nitrogen protection, 10.5 g of L-lactic acid was dehydrated at 130 °C and a vacuum degree of -0.1 MPa for 3 h, and 21 mg of p-toluenesulfonic acid was added, and the reaction was carried out at 170 °C and a vacuum degree of -0.12 MPa for 3 h; (d) After the reaction in step (c) was completed, 4.5 g of L-lactic acid, 1 g of the modified titanium dioxide obtained in step (a) and 20 mL of deionized water were added, and the mixture was reacted at 180°C for 2 h and 230°C for 2 h. The mixture was cooled to room temperature and centrifuged at 10,000 rpm for 20 min. The precipitate was washed with acetone 3 times, with anhydrous ethanol 3 times, and dried in vacuo at 60°C to obtain polylactic acid-TiO 2 .

[0048] This embodiment also provides a biodegradable polyurethane medical examination glove, which is prepared from the polyurethane material.

[0049] A method for preparing biodegradable polyurethane medical examination gloves comprises the following steps: S1: Mix water-based polyurethane emulsion, polylactic acid-TiO 2 , 4-maleimidophenol, dispersant NNO, zinc oxide, ethylenediamine and deionized water were mixed and stirred at 400 rpm for 30 min to obtain a polyurethane material; S2: Prepare a 12wt% calcium chloride aqueous solution as a coagulant, dry the glove mold impregnated with the coagulant at 120°C, and then, when the temperature reaches 50°C, impregnate it into the polyurethane material obtained in step S1, leave it for 60s, and dry it at 110°C for 30 min. After curling and demolding, a biodegradable polyurethane medical examination glove is obtained.

[0050] Example 2: This example provides a polyurethane material, comprising the following raw materials in parts by weight: 80 parts of aqueous polyurethane emulsion, polylactic acid-TiO 2 8 parts, 4-maleimidophenol 0.6 parts, dispersant NNO 0.06 parts, zinc oxide 1 part, ethylenediamine 1 part, deionized water 20 parts.

[0051] The preparation method of waterborne polyurethane emulsion comprises the following steps: (1) Castor oil is dehydrated under vacuum at 100° C. for 2 h, isophorone diisocyanate, polytetramethylene glycol with a molecular weight of 1500 and dibutyltin dilaurate are added, the dibutyltin dilaurate accounts for 0.8wt% of the total mass of castor oil, polytetramethylene glycol and isophorone diisocyanate, the mixture is stirred at 60° C. and 200 rpm for 2 h under nitrogen protection, dimethylolpropionic acid is added, the mixture is reacted at 70° C. for 2 h, acetone is added until the acetone concentration is 10wt%, the mixture is cooled to room temperature, triethylamine is added, and the molar ratio of isocyanate group of isophorone diisocyanate: hydroxyl group in dehydrated castor oil: hydroxyl group in polytetramethylene glycol: hydroxyl group in dimethylolpropionic acid: hydroxyl group in triethylamine is 2.5:1:1:0.6:0.8 to obtain a prepolymer; (2) 1 g of 200 nm silica was mixed with 40 mL of tetrahydrofuran, ultrasonicated at 300 W for 20 min, 3 g of 3-aminopropyltriethoxysilane (APTES) was added, heated in a 70 °C water bath for 5 h, allowed to stand at 4 °C for 2 h, centrifuged at 8000 rpm for 15 min, and the precipitate was dried at 60 °C to obtain modified silica; (3) Dissolve 7.5 g of methyl ferulate in 60 mL of DMF, add 3 g of KOH while stirring, react for 1 h, add 6 g of methyl iodide, heat to 60 °C and react for 2 h, add 300 mL of deionized water, extract three times with ethyl acetate, combine the organic phases, wash the organic phases with saturated NaCl solution, and then wash with anhydrous Na 2 SO 4 The solvent was evaporated at 80 °C and dried at 100 °C. 1 g of the dried product was dissolved in 35 mL of anhydrous ethanol, 175 mL of a 2 mol / L NaOH aqueous solution was added, and the mixture was stirred at 70 °C for 6 h and 10 -3 Mpa, 60℃, concentrated under reduced pressure for 3 h, adjusted the pH to 1.8 with 2 mol / L hydrochloric acid solution, filtered, washed the filter cake with ethanol and deionized water, and dried at 80℃ to obtain modified ferulic acid; (4) 15 mL of tetrahydrofuran and 3 g of the modified ferulic acid obtained in step (3) were mixed to obtain a modified ferulic acid solution, 1.2 g of N,N'-carbonyldiimidazole (CDI) was dissolved in 12 mL of tetrahydrofuran to obtain a CDI solution, and the CDI solution was added dropwise to the modified ferulic acid solution under nitrogen protection at a dropping rate of 0.8 mL / min. After the dropwise addition was completed, the mixture was stirred at 60 rpm for 4 h at room temperature, and then 1.5 g of the modified silica obtained in step (2) was added, and the mixture was stirred for 5 h. The mixture was centrifuged at 8000 rpm for 20 min, and the precipitate was washed 4 times with distilled water and dried at 80°C to obtain hydrophobic particles. (5) 1 g of the hydrophobic particles described in step (4) was mixed with 50 mL of deionized water, and ultrasonicated at 500 W for 40 min to obtain a hydrophobic particle dispersion. 10 g of the hydrophobic particle dispersion was mixed with 20 g of the prepolymer obtained in step (1), and emulsified at 8000 rpm for 2 h to obtain an aqueous polyurethane emulsion.

[0052] Polylactic acid-TiO 2 The preparation method comprises the following steps: (a) 9 g 3-aminopropyltrimethoxysilane (APTMS) and 5 g succinic anhydride were added to 180 mL DMF and mixed. The mixture was stirred at 200 rpm for 3 h at 0°C. 135 mL 40 nm titanium dioxide was added and mixed with DMF at a ratio of 1 g:30 mL. The titanium dioxide DMF suspension was obtained by ultrasonic dispersion at 500W for 20 min. 10.8 mL deionized water was added at the same time. The mixture was stirred for 5 h and centrifuged at 10,000 rpm for 30 min. The precipitate was washed with anhydrous ethanol for 5 times and dried at 80°C to obtain carboxylated titanium dioxide. (b) 9 g of the carboxylated titanium dioxide obtained in step (a) and 3 g of gallic acid were added to 90 mL of DMF, and 0.25 g of p-toluenesulfonic acid was added. The mixture was heated at 50°C for 3 h, and then at 60°C for 10 h. -3 MPa for 2 h, add 180 mL of deionized water, centrifuge at 10000 rpm for 30 min, and dry the precipitate at 80 °C to obtain modified titanium dioxide; (c) Under nitrogen protection, 9 g of L-lactic acid was dehydrated at 110 °C and a vacuum of -0.08 MPa for 2 h, and 9 mg of p-toluenesulfonic acid was added and reacted at 150 °C and a vacuum of -0.08 MPa for 2 h; (d) After the reaction in step (c) was completed, 6 g of L-lactic acid, 1.25 g of the modified titanium dioxide obtained in step (a) and 25 mL of deionized water were added, and the mixture was reacted at 160°C for 1 h and 210°C for 2 h. The mixture was cooled to room temperature and centrifuged at 10,000 rpm for 15 min. The precipitate was washed with acetone 3 times, with anhydrous ethanol 3 times, and dried in vacuo at 60°C to obtain polylactic acid-TiO 2 .

[0053] This embodiment also provides a biodegradable polyurethane medical examination glove, which is prepared from the polyurethane material.

[0054] A method for preparing biodegradable polyurethane medical examination gloves comprises the following steps: S1: Mix water-based polyurethane emulsion, polylactic acid-TiO 2 , 4-maleimidophenol, dispersant NNO, zinc oxide, ethylenediamine and deionized water were mixed and stirred at 300 rpm for 20 min to obtain a polyurethane material; S2: Prepare 8wt% calcium chloride aqueous solution as a coagulant, dry the glove mold impregnated with the coagulant at 100°C, and then, when the temperature reaches 30°C, impregnate it into the polyurethane material obtained in step S1, leave it for 40s, dry it at 80°C for 20 min, and go through the curling and demolding steps to obtain a biodegradable polyurethane medical examination glove.

[0055] Example 3: This example provides a polyurethane material, comprising the following raw materials in parts by weight: 90 parts of aqueous polyurethane emulsion, polylactic acid-TiO 2 10 parts, 4-maleimidophenol 0.8 parts, dispersant NNO 0.08 parts, zinc oxide 1.5 parts, ethylenediamine 1.5 parts, deionized water 25 parts.

[0056] The preparation method of waterborne polyurethane emulsion comprises the following steps: (1) Castor oil is dehydrated under vacuum at 100° C. for 2 h, isophorone diisocyanate, polytetramethylene glycol with a molecular weight of 1500 and dibutyltin dilaurate are added, the dibutyltin dilaurate accounts for 1wt% of the total mass of castor oil, polytetramethylene glycol and isophorone diisocyanate, the mixture is stirred at 60° C. and 250 rpm for 2.5 h under nitrogen protection, dimethylolpropionic acid is added, the mixture is reacted at 70° C. for 2 h, acetone is added until the acetone concentration is 12wt%, the mixture is cooled to room temperature, triethylamine is added, and the molar ratio of isocyanate group of isophorone diisocyanate: hydroxyl group in dehydrated castor oil: hydroxyl group in polytetramethylene glycol: hydroxyl group in dimethylolpropionic acid: hydroxyl group in triethylamine is 2.8:1.2:1:0.8:1, to obtain a prepolymer; (2) 1 g of 250 nm silica was mixed with 40 mL of tetrahydrofuran, ultrasonicated at 300 W for 25 min, 3 g of 3-aminopropyltriethoxysilane (APTES) was added, heated in a water bath at 70 °C for 5.5 h, allowed to stand at 4 °C for 2 h, centrifuged at 8000 rpm for 18 min, and the precipitate was dried at 60 °C to obtain modified silica; (3) Dissolve 7.5 g of methyl ferulate in 70 mL of DMF, add 3 g of KOH with stirring, react for 1 h, add 5.5 g of methyl iodide, heat to 60 °C and react for 2 h, add 350 mL of deionized water, extract three times with ethyl acetate, combine the organic phases, wash the organic phases with saturated NaCl solution, and add anhydrous Na 2 SO 4 The solvent was evaporated at 85 °C and dried at 100 °C. 1 g of the obtained dried product was dissolved in 38 mL of anhydrous ethanol, 190 mL of 2 mol / L NaOH aqueous solution was added, and the mixture was stirred at 70 °C for 6 h and 10 -3 Mpa, 60℃, concentrated under reduced pressure for 3.5 h, adjusted the pH to 2 with 2 mol / L hydrochloric acid solution, filtered, washed the filter cake with ethanol and deionized water, and dried at 80℃ to obtain modified ferulic acid; (4) 15 mL of tetrahydrofuran and 3 g of the modified ferulic acid obtained in step (3) were mixed to obtain a modified ferulic acid solution, 1.5 g of N,N'-carbonyldiimidazole (CDI) was dissolved in 18 mL of tetrahydrofuran to obtain a CDI solution, and the CDI solution was added dropwise to the modified ferulic acid solution under nitrogen protection at a dropping rate of 1 mL / min. After the addition was completed, the mixture was stirred at 70 rpm for 4.5 h at room temperature, and then 1.2 g of the modified silica obtained in step (2) was added, and the mixture was stirred for 5.5 h. The mixture was centrifuged at 9000 rpm for 20 min, and the precipitate was washed 5 times with distilled water and dried at 80°C to obtain hydrophobic particles. (5) 1 g of the hydrophobic particles described in step (4) was mixed with 50 mL of deionized water, and ultrasonicated at 550 W for 50 min to obtain a hydrophobic particle dispersion. 10 g of the hydrophobic particle dispersion was mixed with 25 g of the prepolymer obtained in step (1), and emulsified at 9000 rpm for 2 h to obtain an aqueous polyurethane emulsion.

[0057] Polylactic acid-TiO 2 The preparation method comprises the following steps: (a) 9 g 3-aminopropyltrimethoxysilane (APTMS) and 5 g succinic anhydride were added to 180 mL DMF and mixed. The mixture was stirred at 250 rpm for 3 h at 2°C. 135 mL 50 nm titanium dioxide and DMF were added in a ratio of 1 g:30 mL. The titanium dioxide DMF suspension was obtained by ultrasonic dispersion at 500W for 20 min. 13.5 mL deionized water was added at the same time. The mixture was stirred for 5 h and centrifuged at 10000 rpm for 30 min. The precipitate was washed with anhydrous ethanol for 6 times and dried at 80°C to obtain carboxylated titanium dioxide. (b) 12 g of the carboxylated titanium dioxide obtained in step (a) and 3 g of gallic acid were added to 100 mL of DMF, and 0.22 g of p-toluenesulfonic acid was added. The mixture was heated at 50°C for 3.5 h, and then at 60°C for 10 h. -3 MPa for 2.5 h, add 200 mL of deionized water, centrifuge at 10000 rpm for 30 min, and dry the precipitate at 90 °C to obtain modified titanium dioxide; (c) Under nitrogen protection, 10 g of L-lactic acid was dehydrated at 120°C and vacuum degree of -0.09 MPa for 2.5 h, 15 mg of toluenesulfonic acid was added, and the reaction was carried out at 160°C and vacuum degree of -0.1 MPa for 2.5 h; (d) After the reaction in step (c) was completed, 5 g of L-lactic acid, 1.2 g of the modified titanium dioxide obtained in step (a) and 24 mL of deionized water were added, and the mixture was reacted at 170°C for 1.5 h and 220°C for 2 h. The mixture was cooled to room temperature and centrifuged at 10,000 rpm for 18 min. The precipitate was washed with acetone 3 times, with anhydrous ethanol 3 times, and dried in vacuo at 60°C to obtain polylactic acid-TiO 2 .

[0058] This embodiment also provides a biodegradable polyurethane medical examination glove, which is prepared from the polyurethane material.

[0059] A method for preparing biodegradable polyurethane medical examination gloves comprises the following steps: S1: Mix water-based polyurethane emulsion, polylactic acid-TiO 2 , 4-maleimidophenol, dispersant NNO, zinc oxide, ethylenediamine and deionized water were mixed and stirred at 350 rpm for 25 min to obtain a polyurethane material; S2: Prepare a 10wt% calcium chloride aqueous solution as a coagulant, dry the glove mold impregnated with the coagulant at 110°C, and then, when the temperature reaches 40°C, impregnate it into the polyurethane material obtained in step S1, leave it for 50s, and dry it at 100°C for 25 min. After curling and demolding, a biodegradable polyurethane medical examination glove is obtained.

[0060] The only difference between Comparative Example 1 and Example 1 is that sulfur particles with a D50 of 0.6 μm are used instead of the hydrophobic particles.

[0061] The difference between Comparative Example 2 and Example 1 is that the physical blend of polylactic acid, titanium dioxide and gallic acid is used instead of polylactic acid-TiO 2 , the dosage is the same as in Example 1.

[0062] Experimental Example 1: According to ASTM D412-2006a tensile test method for vulcanized rubber and thermoplastic elastomer, the tensile strength and elongation at break of the medical examination gloves prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The water leakage performance was tested according to EN455-1-2000, and 100 gloves were tested. The results are shown in Table 1.

[0063] Table 1:

[0064] The results in Table 1 show that the tensile strength and elongation at break of Examples 1-3 are higher than those of Comparative Examples 1-2, indicating that the hydrophobic particles of the present invention have good emulsification effect, can form a stable aqueous polyurethane emulsion, promote cross-linking, improve mechanical properties, reduce water leakage, and polylactic acid-TiO 2 Compared with physical mixing, it can increase the degree of cross-linking, improve mechanical properties and reduce water leakage.

[0065] Experimental Example 2: Antibacterial performance test refers to GB15979-2002 Hygiene Standard for Disposable Sanitary Products. The results are as follows: Figure 1 As shown, the accelerated test was carried out in a constant temperature box at 54°C and relative humidity>75% for 14 days, and the antibacterial performance was measured again. The results are as follows Figure 2 shown.

[0066] Figure 1 and Figure 2 The results show that the antibacterial rate of Examples 1-3 is higher than that of Comparative Examples 1-2, and the degree of decrease in antibacterial performance after the accelerated test is lower than that of Comparative Examples 1-2, indicating that the polyurethane material of the present invention has good antibacterial performance and a stable antibacterial effect.

[0067] Experimental Example 3: The degradation rates of the medical examination gloves obtained in Examples 1-3 and Comparative Examples 1-2 were tested according to the method of ASTM D5511-18. The results are as follows: Figure 3 shown.

[0068] Figure 3 The results show that the degradation rate of Examples 1-3 is higher than that of Comparative Examples 1-2, indicating that the hydrophobic particles of modified ferulic acid grafted silica can improve the degradability. 2 The hybrid block containing modified titanium dioxide has better biodegradability.

[0069] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A polyurethane material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of waterborne polyurethane emulsion, 8-12 parts of polylactic acid-TiO2, 0.6-1 parts of 4-maleimidophenol, 0.06-0.1 parts of dispersant NNO, 1-2 parts of zinc oxide, 1-2 parts of ethylenediamine, and 20-30 parts of deionized water; The preparation method of the aqueous polyurethane emulsion comprises the following steps: (1) vacuum dehydrating castor oil, adding isophorone diisocyanate, polytetramethylene glycol and dibutyltin dilaurate, stirring under nitrogen protection, adding dimethylolpropionic acid, reacting, adding acetone, cooling to room temperature, adding triethylamine, and obtaining a prepolymer; (2) mixing silica with tetrahydrofuran, sonicating, adding APTES, heating, standing at 4°C, centrifuging, and drying to obtain modified silica; (3) dissolving methyl ferulate in DMF, adding KOH under stirring, reacting, adding iodomethane, heating, adding deionized water, extracting with ethyl acetate, combining the organic phases, washing with saturated NaCl solution, drying, rotary evaporation, drying, dissolving the dried product in anhydrous ethanol, adding NaOH aqueous solution, stirring, concentrating under reduced pressure, adjusting the pH to 1.8-2.2, filtering with suction, washing the filter cake, and drying to obtain modified ferulic acid; (4) mixing tetrahydrofuran and the modified ferulic acid obtained in step (3) to obtain a modified ferulic acid solution, dissolving CDI in tetrahydrofuran to obtain a CDI solution, adding the CDI solution dropwise to the modified ferulic acid solution under nitrogen protection, stirring after the addition is complete, then adding the modified silica obtained in step (2), continuing to stir, centrifuging, washing, and drying to obtain hydrophobic particles; (5) mixing the hydrophobic particles described in step (4) with deionized water, and subjecting them to ultrasonic treatment to obtain a hydrophobic particle dispersion, and mixing the hydrophobic particle dispersion with the prepolymer obtained in step (1), and emulsifying them to obtain an aqueous polyurethane emulsion; The preparation method of polylactic acid-TiO2 comprises the following steps: (a) APTMS and succinic anhydride are added to DMF and mixed, stirred, titanium dioxide DMF suspension is added, deionized water is added, stirring is continued, centrifuged, washed, and dried to obtain carboxylated titanium dioxide; (b) adding the carboxylated titanium dioxide obtained in step (a) and gallic acid to DMF, adding p-toluenesulfonic acid, heating, reducing pressure, adding deionized water, centrifuging, and drying to obtain modified titanium dioxide; (c) under nitrogen protection, partially dehydrating the L-lactic acid, adding p-toluenesulfonic acid, and reacting; (d) After the reaction in step (c) is completed, the remaining L-lactic acid, the modified titanium dioxide obtained in step (a) and deionized water are added, reacted at 160-180° C., reacted at 210-230° C., cooled, centrifuged, washed and dried to obtain polylactic acid-TiO2.

2. The polyurethane material according to claim 1, characterized in that: In step (1), the molecular weight of the polytetramethylene ether diol is 1500; dibutyltin dilaurate accounts for 0.8-1.2wt% of the total mass of castor oil, polytetramethylene ether diol and isophorone diisocyanate; and the molar ratio of isocyanate group of isophorone diisocyanate: hydroxyl group in dehydrated castor oil: hydroxyl group of polytetramethylene ether diol: hydroxyl group of dimethylol propionic acid: hydroxyl group in triethylamine is 2.5-3:1-1.5:1:0.6-1:0.8-1.

2.

3. The polyurethane material according to claim 2, characterized in that In step (2), the silica particle size is 200-300 nm; the amount ratio of silica to tetrahydrofuran is 1 g:40 mL; and the mass ratio of APTES to silica is 3:

1.

4. The polyurethane material according to claim 3, characterized in that In step (3), the dosage ratio of methyl ferulate to DMF is 1 g: 8-10 mL; the mass ratio of methyl ferulate to KOH is 2.5: 1; the mass ratio of methyl iodide to methyl ferulate is 4: 5-6; the volume ratio of deionized water to DMF is 5: 1; the dosage ratio of the dried product to anhydrous ethanol is 1 g: 35-40 mL; and the volume ratio of NaOH aqueous solution to anhydrous ethanol is 5:

1.

5. The polyurethane material according to claim 4, characterized in that In step (4), the amount ratio of modified ferulic acid to tetrahydrofuran in the modified ferulic acid solution is 1 g:5 mL; the amount ratio of CDI to tetrahydrofuran in the CDI solution is 1:10-15 mL; the mass ratio of modified ferulic acid to CDI is 1:0.4-0.6; and the mass ratio of modified silica to modified ferulic acid is 1:2-3.

6. The polyurethane material according to claim 5, characterized in that In step (5), the ratio of the amount of the hydrophobic particles to the deionized water is 1 g:50 mL; the mass ratio of the hydrophobic particle dispersion to the prepolymer is 1:2-3.

7. The polyurethane material according to claim 6, characterized in that In step (a), the mass ratio of APTMS to succinic anhydride is 9:5; the dosage ratio of APTMS to DMF is 1 g:20 mL; the titanium dioxide particle size is 40-60 nm; in the titanium dioxide DMF suspension, the dosage ratio of titanium dioxide to DMF is 1:30 mL; the dosage ratio of titanium dioxide DMF suspension to APTMS is 15 mL:1 g; and the volume ratio of deionized water to titanium dioxide DMF suspension is 2-3:

25.

8. The polyurethane material according to claim 7, characterized in that In step (b), the amount ratio of the carboxylated titanium dioxide, gallic acid and DMF is 3-5 g:1 g:30-40 mL; the mass ratio of p-toluenesulfonic acid to gallic acid is 1:12-15; the volume ratio of deionized water to DMF is 2:1; in step (c), the amount of L-lactic acid is 60-70wt% of its total amount; the mass ratio of p-toluenesulfonic acid to L-lactic acid is 1-2 mg:1 g; in step (d), the amount ratio of deionized water to modified titanium dioxide is 1 g:20 mL; the mass ratio of the total amount of L-lactic acid to modified titanium dioxide is 12-15:

1.

9. A biodegradable polyurethane medical examination glove, characterized in that: The polyurethane material is prepared from any one of claims 1 to 8.

10. A method for preparing the biodegradable polyurethane medical examination gloves according to claim 9, characterized in that: The following steps are involved: S1: mixing water-based polyurethane emulsion, polylactic acid-TiO2, 4-maleimidophenol, dispersant NNO, zinc oxide, ethylenediamine and deionized water according to weight parts, stirring to obtain a polyurethane material; S2: drying the glove mold impregnated with the coagulant, cooling it, impregnating it with the polyurethane material obtained in step S1, drying it, and undergoing the curling and demoulding processes to obtain a biodegradable polyurethane medical examination glove; the coagulant is a calcium chloride aqueous solution with a concentration of 8-12wt%.

Citation Information

Cited By

  • Hydroxyl-terminated polyester polyol as well as preparation method and application thereof

    CN122465122A